Natural killer cell‐mediated ADCC in SARS‐CoV‐2‐infected individuals and vaccine recipients. Issue 8 (22nd April 2022) - Hagemann, Kerri; Riecken, Kristoffer; Jung, Johannes M.; Hildebrandt, Heike; Menzel, Stephan; Bunders, Madeleine J.; Fehse, Boris; Koch‐Nolte, Friedrich; Heinrich, Fabian; Peine, Sven; Schulze zur Wiesch, Julian; Brehm, Thomas T.; et al.
Abstract: COVID‐19, caused by SARS‐CoV‐2, has emerged as a global pandemic. While immune responses of the adaptive immune system have been in the focus of research, the role of NK cells in COVID‐19 remains less well understood. Here, we characterized NK cell‐mediated SARS‐CoV‐2 antibody‐dependent cellular cytotoxicity (ADCC) against SARS‐CoV‐2 spike‐1 (S1) and nucleocapsid (NC) protein. Serum samples from SARS‐CoV‐2 resolvers induced significant CD107a‐expression by NK cells in response to S1 and NC, while serum samples from SARS‐CoV‐2‐negative individuals did not. Furthermore, serum samples from individuals that received the BNT162b2 vaccine induced strong CD107a expression by NK cells that increased with the second vaccination and was significantly higher than observed in infected individuals. As expected, vaccine‐induced responses were only directed against S1 and not against NC protein. S1‐specific CD107a responses by NK cells were significantly correlated to NK cell‐mediated killing of S1‐expressing cells. Interestingly, screening of serum samples collected prior to the COVID‐19 pandemic identified two individuals with cross‐reactive antibodies against SARS‐CoV‐2 S1, which also induced degranulation of NK cells. Taken together, these data demonstrate that antibodies induced by SARS‐CoV‐2 infection and anti‐SARS‐CoV‐2 vaccines can trigger significant NK cell‐mediated ADCC activity, and identify some cross‐reactive ADCC‐activity against SARS‐CoV‐2 by endemic coronavirus‐specific antibodies. Abstract : Antibodies induced by SARS‐CoV‐2 infection or vaccination mediate NK cell activation, resulting in the release of cytotoxic granules, referred to as ADCC. Highest levels of ADCC were observed when using plasma from BNT162b2‐vaccinated individuals. (Created with BioRender.com)